Country Partnership Framework for the Republic of Djibouti for the Period FY22-FY26 - World Bank Group (World Bank, Washington, DC, 2021)
This Country Partnership Framework (CPF) of the World Bank Group (WBG) for the Republic of Djibouti covers the period from FY22 to FY26. It was prepared in a global and national context marked by the Coronavirus (COVID-19) pandemic. It will support the government’s overarching Vision 2035 and the priorities of the new national strategy, Djibouti Institutions-Connectivity-Inclusion (ICI) for 2020–2024. The WBG program will remain flexible and adaptable to events in a region experiencing volatility, including in Ethiopia, Djibouti’s largest trading partner, and Yemen, located across the Gulf of Aden. The CPF’s overarching objective is to support Djibouti’s goal of reducing poverty through broad-based and inclusive private sector-led growth. The CPF has two focus areas: (1) promoting inclusive private sector-led growth job creation and human capital; and (2) strengthening the role and capacity of the state. In preparing this CPF, the WBG held consultations with key stakeholders in Djibouti, including the government, parliament, private sector, and civil society. Stakeholders encouraged the WBG to play a leading role in supporting the structural reform agenda and helping the country mitigate the challenges posed by the protracted presence of refugees. They underlined the importance of enhancing service delivery and reducing the cost of services, particularly in the telecom/ICT and energy sectors, but also in health and education, public administration, justice, land administration, and the business environment.